Some Tauberian Remainder Theorems for Hölder Summability - Totur, Ümit; Okur, Muhammet Ali (Mathematical modelling and analysis, 2015)
In this paper, we prove some Tauberian remainder theorems that generalize the results given by Meronen and Tammeraid [Math. Model. Anal., 18(1):97-102, 2013] for Hölder summability method using the notion of the general control modulo of the oscillatory behaviour of nonnegative integer order.